Indonesia Diagnosis Related Groups - Rivany, Ronnie (UI Scholars Hub, 2009)
Di Amerika dan Australia, Kelompok Diagnosis Terkait (Diagnosis Related Group’s ) (DRGs) adalah suatu cara mengidentifikasi dan mengelompokkan pasien yang mempunyai kebutuhan dan sumber yang sama dirumah sakit berdasarkan alur perjalanan klinis (Clinical Pathway ). Penyakit yang mempunyai co morbidity atau co mortality, disebut Casemixdan mempunyai kode yang memperlihatkan derajat keparahan kelompok penyakit sehingga secara linear akan mempengaruhi besaran biaya perawatan. Dengan demikian, pembayaran perawatan di rumah sakit akan dilakukan berdasarkan “kesembuhan“ (cost of treatment per diagnosis), dan bukan berdasarkan penggunaan pelayanan medis dan non medis (fee for services). Di Indonesia sampai kini belum ada model perhitungan biaya untuk pembayaran perawatan mulai pasien masuk sampai sembuh dan keluar rumah sakit berdasarkan diagnosis (cost of treatment per diagnosis). Pola pembiayaan yang digunakan di rumah sakit masih didasarkan pada fee for services. Dalam bentuk tesis, konsep Indonesia – DRG/ INA –DRG kami kembangkan di Fakultas Kesehatan Masyarakat Universitas Indonesia, mengacu pada Australian DRG. In America, and Australian, Diagnosis Related Groups, known as DRGs is a method to identify and classify inpatients that have the same resources within hospitals based on Clinical Pathway. It has numbering/coding system used like a menu for determining the cost. The co morbidity and/or co mortality of a di-sease is called the Casemix, where it has numbering/coding that shows the degree of severity, which the cost linearly increased. Therefore the financing is based on the in-patients’ ”recovery” (cost of treatment per diagnosis), and not based on the utility of the medical and non medical treatments (fee for services). One of the issues arise in Indonesia’s health financing system is that it does not have the costing model for health care financing, for inpatients from ad-mission to discharge (cost of treatment per diagnosis). Therefore the financing system used is based on fee for services. Using Australian DRG as reference, the concept of Indonesia–DRG / INA–DRG is developed by the researcher with Graduate Students in the Public Health and Hospital Administration Program, Postgraduate Studies Faculty of Public Health University of Indonesia, in Thesis.